Interfaces and Transformation of Lithuanian Accounting and Statistics - Tamulevičienė, Daiva; Valkauskas, Romualdas (Buhalterinės apskaitos teorija ir praktika, 2018)
[only abstract in English; full article and abstract in Lithuanian]Accounting and statistics are autonomous sciences with specific objects and methods. However, these sciences, as well as practice, have many interconnections: their main objective is to provide objective information to the state and society in order to ensure the country‘s economic growth and social well-being. The article emphasizes that till now the authors of the country did not investigate the relations of accounting and statistics, their links in time flow. There was a lot of time in the flow. There was also the fact that accounting methods found a place in economic-statistical calculations, in practice of statistics.The purpose of the paper is to investigate the features and transformations of the accounting and statistical interfaces in their development stages. The article deals with the interrelations and transformations of Lithuanian accounting and statistics by distinguishing the following stages of their development: 1) Interwar Lithuania (1918 - 1940), 2) Soviet occupation period (1940 - 1990), 3) after the restoration of independence of Lithuania (1990 - 2017). At each stage, the main link between accounting and statistics is highlighted, as well as the essential features of the transformation of these sciences and practices. The article shows that time flow has revealed and reveals new problems in the accounting and statistical interfaces.